AUTONOMOUS UNMANNED HELICOPTER SYSTEM FOR REMOTE SENSING MISSIONS IN UNKNOWN ENVIRONMENTS - T. Merz; S. Chapman (The International Archives of the Photogrammetry, Remote Sensing and Spatial Information Sciences, 2012)
This paper presents the design of an autonomous unmanned helicopter system for low-altitude remote sensing. The proposed concepts and methods are generic and not limited to a speciﬁc helicopter. The development was driven by the need for a dependable, modular, and affordable system with sufﬁcient payload capacity suitable for both research and real-world deployment. The helicopter can be safely operated without a backup pilot in a contained area beyond visual range. This enables data collection in inaccessible or dangerous areas. Thanks to its terrain following and obstacle avoidance capability, the system does not require a priori information about terrain elevation and obstacles. Missions are speciﬁed in state diagrams and ﬂight plans. We present performance characteristics of our system and show results of its deployment in real-world scenarios. We have successfully completed several dozen infrastructure inspection missions and crop monitoring missions facilitating plant phenomics studies.